1999
DOI: 10.1002/(sici)1097-0290(19990420)63:2<129::aid-bit1>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stratification in a fluidized bed bioreactor during treatment of metalworking wastewater

Abstract: During wastewater treatment, biofilm‐coated sand particles stratified in a fluidized bed bioreactor (FBB); particles coated by thicker biofilm segregated toward the top of the bed. Stratification was so well developed that at least two co‐existing regions of significantly different mean biofilm thickness were visually distinct within the operating FBB. The observed stratification is attributed to differences in forces of drag, buoyancy, shear, and collisional impact, as well as differences of collision rate wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 36 publications
0
22
1
2
Order By: Relevance
“…Many authors (Ro and Neethling, 1994;Safferman and Bishop, 1996;Schreyer and Coughlin, 1999;Trinet et al, 1991) observed that the bed becomes stratified due to the presence of granules with different biofilm thicknesses. In such a context, the application of the Richardson and Zaki correlation remains dubious.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors (Ro and Neethling, 1994;Safferman and Bishop, 1996;Schreyer and Coughlin, 1999;Trinet et al, 1991) observed that the bed becomes stratified due to the presence of granules with different biofilm thicknesses. In such a context, the application of the Richardson and Zaki correlation remains dubious.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm has been observed to be relatively smoother and more homogeneous under conditions of high shear (i.e., high liquid velocity) than under low shear conditions (Lau, 1995;Zhang and Bishop, 1994). The study by Schreyer and Coughlin (1999) showed that the introduction of a thinner to increase the shear resulted in a non-stratified bed.…”
Section: Bed Stratificationmentioning
confidence: 99%
“…Although this problem could be serious, research has suggested an easy solution. Applying a high shear stress (high liquid velocity) can make the biofilm thinner and more homogeneous (Zhang and Bishop 1994;Schreyer and Coughlin 1999). Further, Andrews and Tien (1979) indicated that by using a uniform size of support media, the potential for this problem was reduced.…”
Section: Operational Concerns With the Afbr: Do And Bed Stratificationmentioning
confidence: 99%
“…Because CFB has high processing capacity, low pressure drop and good phase dispersion effect, the structure simple and continuous operation easily, it has been widely used in bio-chemical industry, environment, especially metal smelting [1][2][3] . So Experimental study of dynamic characteristics in CFB is very necessary; it is the premise and basis for subsequent amplification experiments and semi-industrial experiments.…”
Section: Introductionmentioning
confidence: 99%